The Relationship Between Body Shaming and Body Image in Female Late Adolescent in Makassar city - Khadijah Latifah Araaf; Muh. Nur Hidayat Nurdin; Irdianti . (Polteknik Ilmu Pemasyarakatan, 2023)
Many adolescents are concerned with their physical appearance and try to look attractive, because of the beauty standards that exist in society. A lot of bullying occurs because individuals look not in accordance with the beauty standards applied by society, one of these bullying is body shaming. In adolescence they experience physical changes, therefore adolescents begin to pay attention to their physical condition and appearance so as not to get body shaming treatment from the social environment. The purpose of this study was to determine the relationship between body shaming treatment and body image of female late adolescents in Makassar City. The sample in this study was female late adolescents in Makassar City who had received body shaming treatment totaling 150 respondents. Data collection was conducted using two research instruments, namely, body shaming scale and body image scale. Hypothesis testing used Spearman Rho correlation analysis. The results showed that there was no relationship between body shaming and body image, r = -0.034 (p = 0.680). This means that H1 is rejected and H0 is accepted. The implication in this study is that adolescents are expected to appreciate and accept their body appearance as it is and appreciate differences in appearance that do not match the beauty standards made by society.